Caviomorph rodents: main features of their evolution. - Vucetich, María G. (2016)
The rich fossil record of caviomorph rodents provides good basis for understanding the major trends of their evolution in southern South America. The most important features of their evolutionary history are here analyzed since their entrance during the middle Eocene by rafting from Africa. The initial radiation of caviomorphs was complex, with the differentiation of taxa that cannot be assigned to any of the major clades (Octodontoidea, Erethizontoidea, Cavioidea, and Chinchilloidea). The evolutionary history occurred through pulses of radiation, being the most important those of the middle? Eocene–early Oligocene, late Oligocene, and middle to late Miocene.